Buletin Majlis Penghuni Desasiswa Tekun Sidang Akademik 2024/2025 Semester 1 - Majlis Penghuni Desasiswa Tekun Universiti Sains Malaysia (Majlis Penghuni Desasiswa Tekun Universiti Sains Malaysia, 2025)
The 2030 Agenda for Sustainable Development, 17 Sustainable Development Goals (SDGs), Reduced inequalities (SDG 10), Peace, justice, and strong institutions (SDG 16), Climate action (SDG 13), Quality education (SDG 4), Good health and well-being (SDG 3), Partnerships for the goals (SDG 17).